2002
DOI: 10.1128/jcm.40.4.1140-1145.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus gilvus sp. nov. and Enterococcus pallens sp. nov. Isolated from Human Clinical Specimens

Abstract: Light yellow-pigmented (strain PQ1) and yellow-pigmented (strain PQ2), gram-positive, non-spore-forming, nonmotile bacteria consisting of pairs or chains of cocci were isolated from the bile of a patient with cholecystitis (PQ1) and the peritoneal dialysate of another patient with peritonitis (PQ2). Morphologically and biochemically, the organisms phenotypically belonged to the genus Enterococcus. Whole-cell protein (WCP) analysis and sequence analysis of a segment of the 16S rRNA gene suggested that they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 23 publications
0
33
2
Order By: Relevance
“…However, the other ATP-secreting enterococcus, E. faecium, is important for nosocomial infections (24,25). E. gilvus was isolated from the bile of a patient suffering from cholecystitis (pathogenic role is unclear) (26), and E. cecorum is associated with endocarditis (27). Therefore, ATP-secreting enterococci might be considered clinically problematic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other ATP-secreting enterococcus, E. faecium, is important for nosocomial infections (24,25). E. gilvus was isolated from the bile of a patient suffering from cholecystitis (pathogenic role is unclear) (26), and E. cecorum is associated with endocarditis (27). Therefore, ATP-secreting enterococci might be considered clinically problematic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven isolates, obtained from Lisbon Veterinarian Faculty, were reported as dog-infecting strains. When phenotypic and molecular methods (6,33,35) The species E. villorum (45), E. haemoperoxidus and E. moraviensis (40), E. porcinus and E. ratti (43), and E. pallens and E. gilvus (44) were not included in the study, since they have been proposed and accepted as new species more recently.…”
Section: Microorganismsmentioning
confidence: 99%
“…Enterococcus faecalis causes 80 to 90% of human enterococcal infections, and E. faecium accounts for the majority of the remainder. Other enterococcal species, including E. avium, E. casseliflavus, E. durans, E. gallinarum, E. gilvus, E. hirae, E. malodoratus, E. mundtii, E. pallens, E. raffinosus, and E. solitarius, are infrequent causes of human infection (29,30,31,34,37,44).…”
mentioning
confidence: 99%
“…Int J Food Microbiol (in press). Characters are based on those obtained in the present study and/ or reported elsewhere (Devriese et al, 1993;Tyrrell et al, 2002). …”
mentioning
confidence: 99%